Pengaruh Korean Wave Dan Brand Ambassador Terhadap Keputusan Pembelian Produk Somethinc (Studi Kasus Pada Mahasiswi Institut Stiami Pusat Jakarta Angkatan 2019-2022) - Izzah, Nidaul; Febriyanti, Yuni (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The Korean Wave phenomenon involving the popularity of Korean culture has created an impact on consumer preferences in various parts of the world. Apart from that, the use of Brand Ambassadors, especially those from the Korean entertainment industry, is also an important factor in shaping consumer perceptions and purchasing decisions regarding Somethinc products. This study aims to analyze the influence of Korean Wave and Brand Ambassador on the decision to purchase Somethinc products Case Study on female students of Institut STIAMI Pusat Jakarta batch 2019-2022. This type of research is a quantitative research using descriptive methods, as well as sampling techniques used are purposive sampling. Data collection techniques by providing questionnaires to respondents, observation, and literature studies. The data analysis used is multiple linear regression analysis processed using SPSS version 26. The results of this study show that the variables Korean Wave (X1), Brand Ambassador (X2) simultaneously have a significant effect on the purchase decision (Y) of somethinc products for students of the Institut Stiami Pusat Jakarta batch 2019-2022. Korean Wave variables partially positively and significantly affect the purchase decision, while the brand Ambassador variables partially positively and significantly affect the purchase decision.